Palladium Decorated N-Doped Carbon Foam as a Highly Active and Selective Catalyst for Nitrobenzene Hydrogenation - Prekob Ádám; Szamosvölgyi Ákos; Muránszky Gábor; Lakatos János; Kónya Zoltán; Fiser Béla; Bela Fiser; Фішер Бейло; Viskolcz Béla; Vanyorek László (MDPI, 2022)
Abstract. Carbon foam was synthesized by the carbonization of 4-nitroaniline. The reaction is an alternative of the well-known “carbon snake” (or sugar snake) demonstration experiment, which leads to the formation of nitrogen-doped carbon foils due to its nitrogen content. The synthesized carbon foils were grinded to achieve an efficient catalyst support. Palladium nanoparticles were deposited onto the surface of the support, which showed continuous distribution. The prepared Pd nanoparticle decorated carbon foils showed high catalytic activity in nitrobenzene hydrogenation. By applying the designed catalyst, total nitrobenzene conversion, a 99.1 n/n% aniline yield, and an exceptionally high selectivity (99.8 n/n%) were reached. Furthermore, the catalyst remained active during the reuse tests (four cycles) even without regeneration.
Editorial Board: https://www.mdpi.com/journal/ijms/editors
Contents: https://www.mdpi.com/1422-0067/23/12
Keywords: carbon foils; aniline; carbon snake; catalytic hydrogenation; catalyst support